Optimization of culture conditions by Response Surface Methodology and Unstructured kinetic modeling for L-Asparaginase production by Pseudonocardia endophytica VUK-10 - Ushakiranmayi Managamuri, M. Vijayalakshmi, V. S. Rama Krishna Ganduri & , R. Satish Babu, Sudhakar Poda (Journal of Applied Pharmaceutical Science, 2017)
L-asparaginase is an anti-tumor enzyme and widely accepted as chemotherapeutic agent which has activity against acute lymphoblastic leukemia. The current study targets the production of L-asparaginase by Pseudonocardia endophytica VUK-10 by a statistically designed model. Experiments were performed according to central composite design of RSM with five independent variables such as time, pH, temperature, concentrations of maltose and L-asparagine concentration for optimization. All the five conditions had significant interaction with other variables for the maximum response (L-asparaginase production). Maximum L-asparaginase production was recorded as 7.42 IU/ml slightly higher than the model predicted value of 6.8 IU/ml, from statistical optimization studies. An unstructured kinetic model was proposed to depict the profiles of biomass, substrate utilization and L-asparaginase production in optimized medium under shake flask level. The logistic and Leudeking-Piret expressions were modified to predict the kinetic model parameters (µmax, X0, Xmax, α, β, γ and η) and we found that L-asparaginase production was growth-associated. High significant correlation (R2) values of 0.86, 0.96 and 0.94 were observed with the experimental and predicted results for Pseudonocardia endophytica VUK-10 growth, L-asparaginase activity and Maltose utilization, respectively. The results obtained from medium optimization using RSM and unstructured mathematical models describe the L-asparaginase fermentation kinetics more effectively.
Keywords: L-asparaginase,Optimization,Response Surface Methodology,Unstructured kinetic model,Pseudonocardia endophytica VUK-10.